Coil‐occlusion of the left ventricle as emergency treatment in failing stage I palliation for hypoplastic left heart syndrome with sinusoids1. Issue 1 (2nd May 2012) - Hummel, Johanna; Stiller, Brigitte; Grohmann, Jochen
Abstract We report on a patient with hypoplastic left heart syndrome (HLHS), ventricular septal defects, and coronary sinusoids who suffered recurrent myocardial ischemic events that required cardiopulmonary resuscitation after stage I palliation. We identified the main reason to be a steal phenomenon of blood from the left coronary artery via the sinusoids into the rudimentary left ventricle and across the septal defects into the right ventricle. To limit this coronary steal phenomenon, we successfully performed transcatheter closure of the left ventricle with implantation of three Microplex Terumo®‐Coils. This led to the patient's clinical stabilization. Stage II surgery took place at the age of 5 months without difficulty. In the setting of a symptomatic neonate with HLHS and ventriculocoronary connections, embolization of the left ventricle is a feasible interventional therapy. © 2012 Wiley Periodicals, Inc.